Studi Toksisitas Nanopartikel Organ Limpa pada Hewan Percobaan, Tinjauan Scoping Review - Dodi Faras Ilmiawan Sutomo; Dwi Nur Ahsani; Ika Fidianingsih (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
Nanotechnology has been developing in the medical field, but some nanoparticles have toxic effects on the body, including the spleen. This scoping review represents an attempt to take stock of existing research results related to the presence or absence of toxicity to the spleen caused by nanoparticles involving experimental animals. A scoping review was conducted to synthesize and map the toxicity of nanoparticles. It has been searched on PubMed databases for spleen or lien and toxic or toxicity, and nanoparticles or dendrimers or "metal nanoparticles" or “magnetite nanoparticles” or nanoshells or “multifunctional nanoparticles” or nanocapsules or nanoconjugates or nanodiamonds or nanogels or nanospheres. Seventeen studies met our inclusion criteria. In conclusion, it showed that 13 nanoparticles could cause toxicity in rodent spleen and as many as 4 nanoparticles did not cause toxicity in rodent spleen.